Livestock and Climate Change: Outlook for a more sustainable and equitable future - Thornton, Philip K.; Wollenberg, Eva K.; Cramer, Laura K. (International Livestock Research Institute, 2024)
The livestock sector will need to simultaneously meet future consumer demand while supporting net zero targets by 2050, survive increasing frequency and severity of climate change hazards, and achieve outcomes for water, biodiversity, social resilience and economic development. 2. Climate change therefore requires a new trajectory for the development of the livestock sector. The economic role of livestock may shift significantly, and we need to anticipate a just transition of livestock farmers to other livelihood activities. 3. Trends in livestock demand and supply under climate change are likely to become more uncertain and equity and productivity gaps are likely to intensify in the coming decades. Although industrialised systems can better invest in the feed and adaptations and mitigation measures needed under climate change than smallholders’ systems, livestock are critical for smallholders’ livelihoods and food security, and we need to anticipate the wider range of interventions that may be needed to increase resilience in such systems. 4. Future livestock and climate development needs to be planned and implemented in a cross-sectoral way. The multi-dimensional importance of livestock to the livelihoods of at least 1.3 billion people globally has not yet been reflected in development or climate assistance, research focus or the data landscape. 5. Under climate change, there are no one-size-fits-all policy and technological responses, nor are there any silver bullets. There are multiple, often competing discourses around the climate-livestock-livelihood nexus and responses need to be appropriate for local contexts while contributing to national and global targets. 6. Many management options are available to help livestock farmers in lower-income countries adapt to climate change, including diversification of livestock species and breeds; integration of livestock with forestry, crop and aquaculture production; improving livestock diets; modifying animal health and heat stress management strategies; and changing the timing and location of farm operations. 7. Institutional, policy and technological opportunities for increasing livestock farmers’ adaptive capacity include preserving livestock mobility traditions in pastoral lands; assistance with destocking and restocking before and after drought; developing new product markets to satisfy consumer demand; promoting wider use of index-based insurance products and other risk transfer mechanisms; and enhancing farmers’ effective use of extension information using social media and digital platforms. 8. The viability of options to adapt and increase adaptive capacity is highly dependent on local contexts that are often characterized by capital, land and labour constraints and limited accessibility and knowledge. And in the face of longer-term climate change, the limits to the effectiveness of such options are often unknown. 9. Additional management options are available to help livestock farmers in lower-income countries mitigate greenhouse gas emissions or sequester carbon, including intensified production with fewer animal numbers, managing herd composition, shifting to lower-emission types of livestock, silvopastoralism, grassland restoration, avoided burning of grasslands, and low-emission breed selection. Along the supply chain, more efficient and renewable energy in the cold chain is a major option for mitigation. While additional measures such as feed additives, manure management or alternative proteins also can reduce methane, these technologies are not yet available, affordable or relevant to many lower-income farmers. Vaccines and manipulation of the rumen microbiome are promising technologies for the future.